Evaluation of oral nano-curcumin efficacy on respiratory function and quality of life in patients with bronchial non-atopic asthma: A randomized controlled trial - Shahrzad Mohammadzadeh Lari; Amir Houshang Mohamadpour; Davood Attaran; Mahmodreza Jafari; Omid Arasteh; Maryam Emadzadeh; Mahnaz Mozdourian; Soroush Attaran; Zahra Javidarabshahi (Mashhad University of Medical Sciences, 2024)
Objective: Asthma is a common disease and curcumin has modest effect in inflammatory disorders. This study investigated the efficacy of nano-curcumin on asthma.Materials and Methods: In this double-blinded randomized clinical trial, 60 patients with non-atopic bronchial asthma were randomly stratified in two groups of intervention (N=30) and control (N=30) groups. Apart from their standard treatment, the intervention group received 40 mg nano-curcumin (soft gel) three times daily while the control group received placebo. During the 60-day study, patients were assessed using spirometry to measure Forced expiratory volume in first second (FEV1). Asthma control test (ACT) was completed every 30 days and asthma quality of life questionnaire (AQLQ) was completed at the first and end of the study.Results: Totally, 31 patients (51.7%) were male and the mean age was 51.45±12.58 years. FEV1 was improved but there was no significant difference between intervention and control groups. ACT and AQLQ domains scores significantly improved. However, it was not statistically different between control and intervention groups.Conclusion: Nano-curcumin at administered dosage had no additive effect on the standard treatment in asthmatic patients.